Huwelik en huweliksrolle in Afrikaanse kultuur- en kerklike konteks - Botha, Annelie (HTS teologiese studies, 2013)
Marriage and marital roles in the Afrikaans cultural and religious context. The article investigates women’s socialization in terms of their position in society and the church, and their roles in the marriage relationship. A brief historical overview is given of how the understanding of marriage has developed, with specific emphasis on marriage and marital roles in Afrikaans cultural and religious contexts. The authors examine the ecclesiastical magazines Die Hervormer and Die Jaarboek van die Nederduitsch Hervormde Sustersvereniging (Yearbook of the Netherdutch Reformed Women’s Association). The article shows that the message communicated to women who are members of the Netherdutch Reformed Church with regard to marital roles is that they must be submissive. Centuries of conditioning has created submissiveness and inferiority in these women and this has affected them negatively not to be equal to men in society and marriage relationships.